"My dad is Li Gang!" or seeing the state: transgressive mobility, collective visibility, and playful corruption in contemporary urban China. Issue 1 (2nd January 2017) - Notar, Beth E.
Abstract : This article examines transgressive mobility in contemporary urban China to argue that traffic does not just provide an analogy for inequality and abuse of power, but that it is through street spectacle that people see power enacted. While state power (à la Virilio) seeks to control the circulation of people, things, and ideas, state officials and their kin exhibit their power through transgressing this control. Examination of the "My dad is Li Gang!" case – where the son of a district police chief claimed immunity from prosecution after a hit-and-run accident because of his father's position – as well as participant observation of street crossing in the city of Kunming, illustrate that people use collective observation, language and action to critique the transgressive mobility of officials and their kin. Yet, at the same time, a rising upper middle class who can now legally purchase their own cars aspire to the luxurious lifestyles of officials and their kin by "playing at corruption" through their own transgressive mobility of elite drag racing.